Pengaruh konsumsi mentimun (cucumis sativus) dan semangka (citrullus lanatus) terhadap tekanan darah pada penderita hipertensi dengan penyakit penyerta - Dhamayanti, Meta Saskia Rina; Maliya, Arina (Holistik Jurnal Kesehatan, 2024)
Background: Hypertension is one of the major causes of premature death throughout the world. Blood pressure causes several risk factors that attack the heart and blood vessels such as the brain. In order to prevent more severe complications such as heart, kidney and brain disease, early prevention is needed. Management of hypertension uses two methods, namely pharmacological and non-pharmacological methods. Purpose: To identify differences in the usefulness of cucumber juice and watermelon juice regarding blood pressure in individuals with hypertension with comorbidities. Method: Quantitative research uses a pre-experimental approach with a pre-post-test group design. The research was conducted at the Kartasura Community Health Center in January-February 2024 on 30 hypertension sufferers using purposive sampling. The sample was divided into two groups, namely, 15 respondents in the cucumber group and 15 respondents in the watermelon group. The intervention was carried out for 7 days consistently in the morning. Data analysis used univariate and bivariate with the Wilcoxon and Mann-Whitney U statistical tests. Results: There was an effect of consumption of cucumber juice on systolic blood pressure (α 0.001) and diastolic blood pressure (α 0.021) with an average pre-test value of 169.33/89.33 mmHg and post-test 141.33/83.33 mmHg. Meanwhile, in the group given watermelon juice, there was an influence on systolic blood pressure (α 0.001) or diastolic blood pressure (α 0.001) with pre-test values ​​of 152/93.33 mmHg and post-test 125.33/77.33 mmHg. From the Mann-Whitney U test, there was a difference between giving cucumber juice and watermelon juice on systolic blood pressure (α 0.012) or diastolic blood pressure (α 0.026).. Conclusion: There is a difference in the effectiveness of cucumber juice treatment in reducing systolic blood pressure while the watermelon juice team has effectiveness in reducing diastolic blood pressure.   Keywords: Cucumber (cucumis sativus); Comorbid; Hypertension; Watermelon (cucumis sativus).   Pendahuluan: Hipertensi menjadi salah satu penyebab besar kematian dini seluruh dunia. Tekanan darah menyebabkan beberapa faktor risiko yang menyerang jantung dan pembuluh darah seperti otak. Guna mencegah adanya komplikasi yang lebih parah seperti jantung, penyakit ginjal dan otak diperlukan pencegahan dini. Penatalaksanaan hipertensi menggunakan dua metode yaitu dengan farmakologi dan metode non farmakologi. Tujuan: Untuk mengidentifikasi perbedaan kegunaan jus mentimun dan jus semangka mengenai tekanan darah penderita hipertensi dengan penyakit penyerta. Metode: Penelitian kuantitatif menggunakan pendekatan pra-eksperimental dengan desain kelompok pre-post-test. Penelitian dilakukan di Puskesmas Kartasura pada bulan Januari-Februari 2024 kepada 30 penderita hipertensi menggunakan pengumpulan purposive sampling. Sampel dibagi menjadi dua kelompok yakni, 15 responden kelompok mentimun dan 15 responden kelompok semangka. Intervensi dilakukan selama 7 hari secara konsisten pada pagi hari. Analisa data menggunakan univariat dan bivariat dengan uji statistik Wilcoxon dan Mann-Whitney U. Hasil: Terdapat pengaruh pemberian jus mentimun terhadap tekanan darah sistolik (α 0.001) dan tekanan darah diastole (α 0.021) dengan rata-rata nilai pre-test 169.33/89.33 mmHg dan post-test 141.33/83.33 mmHg. Sedangkan pada kelompok pemberian jus semangka terdapat pengaruh tekanan darah sistolik (α 0.001) ataupun tekanan darah diastole (α 0.001) dengan nilai pre-test 152/93.33 mmHg dan post-test 125.33/77.33 mmHg. Dari uji Mann-Whitney U terdapat perbedaan pemberian jus mentimun dengan jus semangka terhadap tekanan darah sistolik (α 0.012) ataupun tekanan darah diastole (α 0.026). Simpulan: Ada perbedaan kegunaan perlakuan jus mentimun terhadap penyusutan tekanan darah sistolik, sedangkan kelompok  jus semangka terdapat efektivitas terhadap penyusutan tekanan darah diastolik.   Kata Kunci: Hipertensi; Jus Semangka; Jus Mentimun; Komorbid; Tekanan Darah.